Smart Cat Home Dengan Sistem Kontrol yang menggunakan Aplikasi Telegram - Alfi Safira Anandatito Putri (Politeknik Negeri Malang, 2019)
Survey data by the World Society for the Protection of an Animal(WSPA) in 2007 recorded that total pet population in Indonesia was 23,000,000 individuals (Batson,2008). The majority of Indonesian choose to keep purebred cats. Care of this breed is'nt easy and requires special attention from the owner. With Smart Cat Home, cat owners can monitor and control feeding schedule, temperature, and drinking conditions in cat cage via their telegraphic social media. The Smart Cat Home is designed using Raspberry Pi3 microcontroller. This system functions to monitor feeding schedule according to cat habits, determine weight of cat feed detected by Loadcell, monitor availability of drinking water by water level sensor, capture cat's condition by webcam, and temperature monitoring using DHT11 sensor. All conditions on system will be displayed on Telegram Bot. From test results can be concluded that the whole system works well. In temperature system, the warmer will be active when <22°C, and the fan will be active at temperature >26°C. In feeding system, the weight sensor is able to read feed weight accurately. From 5 data on feed weight, the average feed weight is 78 grams. In drinking system, the drinking water reservoir will fill drinking container when water level sensor have voltage value <1600 mv with water level of 2.5cm from the surface. From the calculation of delay value in sending data, there's delay of 33.8ms. Packet loss or the amount of data lost during transmission process is 0.3%. Througput of data transmission in system is 84,139,041 Kbytes/sec.